Butorphanol as an Adjuvant to Ropivacaine for Adductor Canal Blocks in Total Knee Arthroplasty Patients: A Randomized, Double, Blind Study. (14th October 2022) - Mu, Tong; Liu, Danyan; Gao, Fei
Abstract : Background . The objective of this study was to observe the effects of butorphanol as an adjuvant to ropivacaine for the adductor canal block (ACB) on postoperative analgesia in patients undergoing total knee arthroplasty (TKA). Methods . Seventy-four patients undergoing TKA were included and randomly divided into two groups: Group BR received 20 ml of 0.33% ropivacaine plus 1 mg butorphanol and Group R received 20 ml of 0.33% ropivacaine plus 1 ml normal saline for ultrasound-guided adductor canal blocks. The primary outcomes were the duration of the sensory block and the pain visual analogue scale (VAS), and secondary outcomes included the number of PCIA attempts (patient-controlled intravenous analgesia) and the time to first pressing and rescue analgesia. Other outcomes included knee active range of motion (ROM), quadriceps strength, the time to first mobilization, the duration of postoperative hospital stay, Knee Society Score (KSS), and postoperative complications. Results . Since two patients in each group rejected postoperative assessments, 35 patients were included in each group. Compared with Group R, Group BR had longer duration of sensory blocks (18.42 ± 3.46 vs. 15.36 ± 2.29 h, p < 0.01 ) and lower postoperative pain scores within 24 hours at rest and within 12 hours with activity (p < 0.01 ). The number of PCIA attempts decreased within 48 hours after surgery (4.5 ± 1.2 vs. 7.8 ± 1.5 times, p < 0.01 ), and the time to first pressing was later (20.31 ± 2.59 vs. 16.25 ± 2.31 h, p < 0.01 ). In addition, Group BR had bigger knee ROM at within 24 hours after the operation than Group R (68.37 ± 4.70°vs. 59.21 ± 6.41, 85.67 ± 5.17 vs. 74.37 ± 4.68°, 97.62 ± 5.43 vs. 84.18 ± 4.49°, p < 0.01 ). There was no significant difference between the two groups (p > 0.05 ) in terms of rescue analgesia, quadriceps strength, the time to first mobilization, the duration of postoperative hospital stay, the KSS function scores, and postoperative complications. Conclusions . Butorphanol plus ropivacaine ultrasound-guided adductor canal block can prolong the duration of sensory block, relieve early postoperative pain, and improve the range of motion of the knee joint, without affecting the occurrence of postoperative complications. Name of the Registry . Chinese Clinical Trial Registry. Trial Registration Number . ChiCTR2100041859 . URL of Trial Registry Record . http://www.chictr.org.cn/edit.aspx?pid=119731&htm=4. Date of Registration . 08/01/2021 0:00:00.